Comparing exergames and aerobic exercise: Evaluation of the effects on emotions and executive functions - Anna Maria Mariani; Emanuele Marsico; Sarah Caglioti (Pensa MultiMedia, 2022)
The study presented aims to investigate the impact of a balance training conducted by exergames on some domains of a cognitive and affective nature, in a sample of university students (average age 28 ± 6). In this sense, executive functions, selective attention and subjective emotional state were evaluated. These constructs were chosen because of their centrality in fostering learning processes. The effects of exergaming were compared with those obtained through aerobic training of the same duration (20 min). The results showed a similar impact of the two types of training on the cognitive domains under analysis, while a statistically difference was observed with respect to higher levels of dominance (<0.05) in the post-test exergames measured. through the SAM (Self-Assessment Manikin). The research carried out has allowed to highlight the opportunity to use these tools in the implementation of positive affectivity in young adults. On the basis of the results obtained, it is therefore possible to set future research directions relating to the study of the effects of exergames on constructs related to the dominance, such as self-esteem and self-efficacy and the relationship of these with high-level cognitive functions, whose integration is necessary for the structuring of learning programs in different training contexts.